First proficiency testing for NGS‐based and combined NGS‐ and FISH‐based detection of FGFR2 fusions in intrahepatic cholangiocarcinoma. (12th January 2023) - Neumann, Olaf; Lehmann, Ulrich; Bartels, Stephan; Pfarr, Nicole; Albrecht, Thomas; Ilm, Katharina; Christmann, Jens; Volckmar, Anna‐Lena; Goldschmid, Hannah; Kirchner, Martina; Allgäuer, Michael; Walker, Maria; et al.
Abstract: Intrahepatic cholangiocarcinoma harbours druggable genetic lesions including FGFR2 gene fusions. Reliable and accurate detection of these fusions is becoming a critical component of the molecular work‐up, but real‐world data on the performance of fluorescence in situ hybridisation (FISH) and targeted RNA‐based next‐generation sequencing (NGS) are very limited. Bridging this gap, we report results of the first round robin test for FGFR2 fusions in cholangiocarcinoma and contextualise test data with genomic architecture. A cohort of 10 cholangiocarcinoma (4 fusion positive and 6 fusion negative) was tested by the Institute of Pathology, University Hospital Heidelberg, Germany. Data were validated by four academic pathology departments in Germany. Fusion‐positive cases comprised FGFR2 :: BICC1, FGFR2 :: DBP, FGFR2 :: TRIM8, and FGFR2 :: ATE1 fusions. In a second step, a round robin test involving 21 academic and non‐academic centres testing with RNA‐based NGS approaches was carried out; five participants performed FISH testing in addition. Thirteen of 16 (81%) centres successfully passed the NGS only and 3 of 5 (60%) centres passed the combined NGS + FISH round robin test. Identified obstacles were bioinformatic pipelines not optimised for the detection of FGFR2 fusions and assays not capable of detecting unknown fusion partners. This study shows the benefit of targeted RNA‐NGS for the detection of FGFR2 gene fusions. Due to the marked heterogeneity of the genomic architecture of these fusions, fusion partner agnostic (i.e. open) methodological approaches that are capable of identifying yet unknown fusion partners are superior. Furthermore, we highlight pitfalls in subsequent bioinformatic analysis and limitations of FISH‐based tests.